The use of the software JST-XRD for identification of crystalline phases in pharmaceutical raw materials and tablets - Julia Sawaki Tanaka; Simone Toledo Bonemer de Salvi; Selma Gutierrez Antonio; Carlos Oliveira Paiva-Santos (São Paulo State University (UNESP), 2016)
Study of polymorphism is of great importance for the pharmaceutical industry once polymorphs may display different physicochemical properties, which, in turn, may result in stability differences that can bring problems for the manufacturing stages and the quality of final products. Although research on organic polymorphs has greatly increased in the last decades, it still does not cover all needs for the pharmaceutical market. Techniques such as spectroscopy in the infrared region, nuclear magnetic resonance, thermal analysis, X-ray diffraction, etc., can be used to identify polymorphism. The polymorphism is a property of the crystalline solid state, and can be evaluated by X-ray diffraction once each polymorph exhibits one specific X-ray diffraction pattern. The JST-XRD program is a tool designed to help the identification of crystalline phases (including polymorphs) present in pharmaceutical ingredients and tablets by using X-ray diffraction data obtained from scientific articles and patents. This paper presents new implementations for the JST-XRD and describes its use in the analysis of active pharmaceutical ingredient and marketed tablets of norfloxacin, mebendazole and atorvastatin calcium. By the means of comparison, JSTXRD allowed identifying the crystalline phases in the diffraction patterns of the analyzed drugs, showing the program suitability for polymorphism research, pre-formulation and quality control in pharmaceutical industries. JST-XRD can also be used for educational purposes in undergraduate and graduate programs in order to show the potentiality of X-ray powder diffraction in polymorphism analysis.